PENERAPAN STRATEGI PEMBELAJARAN TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN LARUTAN ASAM DAN BASA DI KELAS XI NEGERI 2 BANTAN - Suzanawati '; Miharty '; Armiyus Thaib Thaib (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to increase student result of learning on the subject of alkalin acid solution in class XI SMA Negeri 2 Bantan. Form of research is experiment research with pretest-posttest design. The sample consisted of two classes, XI IPA2 as an experiment class and XI IPA1 as a control class randomly selected after tests of normality and homogeneity. Experiment class was given to applied Talking Stick while the control class was not. Data analysis technique is used t-test. Based on the results of final processing data use t-test formula obtained  tcount>ttable is 2,503>1,67, it means that the applying of Talking Stick can improve student result of learning on the subject of alkalin acid solution in class XI SMA Negeri 2 Bantan. The improvement student result of learning on the subject of alkaline acid solution is 9,45%. Keywords : Talking Stick, Result of Learning